2017
DOI: 10.1002/erv.2518
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Adults with Binge Eating Disorder Based on Severity Levels

Abstract: The clinical utility of the severity criterion for binge eating disorder (BED), introduced in the DSM-5 as a means of addressing heterogeneity and variability in the severity of this disorder, was evaluated in 189 treatment-seeking adults with (DSM-5) BED. Participants classified with mild, moderate, severe and extreme severity of BED, based on their weekly frequency of binge eating episodes, differed significantly from each other in body mass index (BMI), eating disorder features, putative factors involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 78 publications
(216 reference statements)
5
19
0
Order By: Relevance
“…The DSM ‐5 introduced new dimensional severity ratings for EDs, yet research that tested the validity and utility of the DSM ‐5 severity indices for EDs has been mixed. Studies found that severity indices did not meaningfully differentiate clients on the basis of psychosocial impairment or associated psychopathology (Jenkins, Luck, Cardy, & Staniford, ; Machado, Grilo, & Crosby, ; Reas & Rø, ; Smith et al, ), showed mixed support (Gianini et al, ; Grilo, Ivezaj, & White, b), or found that severity indices were significant predictors of important outcomes (Dakanalis, Colmegna, Riva, & Clerici, ; Dakanalis, Riva, Serino, Colmegna, & Clerici, ; Grilo, Ivezaj, & White, ). A limitation of the severity dimensions for EDs is that they ignore important trans‐diagnostic information about non‐ED aspects of internalizing psychopathology that may be the focus of clinical attention, such as suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…The DSM ‐5 introduced new dimensional severity ratings for EDs, yet research that tested the validity and utility of the DSM ‐5 severity indices for EDs has been mixed. Studies found that severity indices did not meaningfully differentiate clients on the basis of psychosocial impairment or associated psychopathology (Jenkins, Luck, Cardy, & Staniford, ; Machado, Grilo, & Crosby, ; Reas & Rø, ; Smith et al, ), showed mixed support (Gianini et al, ; Grilo, Ivezaj, & White, b), or found that severity indices were significant predictors of important outcomes (Dakanalis, Colmegna, Riva, & Clerici, ; Dakanalis, Riva, Serino, Colmegna, & Clerici, ; Grilo, Ivezaj, & White, ). A limitation of the severity dimensions for EDs is that they ignore important trans‐diagnostic information about non‐ED aspects of internalizing psychopathology that may be the focus of clinical attention, such as suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in clinical samples with BED found levels of several measures of eating pathology increased across the severity groups (Dakanalis, Riva, Serino, Colmegna, & Clerici, ; Gianini et al, ; Grilo, Ivezaj, & White, ), but participants with BED in these studies were mostly obese. Although the prevalence of obesity in Japan is about one‐eighth of the United States, the number of patients with BED has been increasing.…”
Section: Introductionmentioning
confidence: 88%
“…In psychiatry, considering psychopathology as dimensional traits may better depict inter-individual differences (Kozak & Cuthbert, 2016). The 5th version of Diagnostic and Statistical Manual of Mental Disorders (DSM-5) has also introduced severity levels for binge eating disorder, a clinical manifestation of uncontrolled eating (Dakanalis et al, 2017). Preclinical levels of uncontrolled eating might also vary on a spectrum (Davis, 2013).…”
Section: Uncontrolled Eating As a Continuummentioning
confidence: 99%